H+-capacitor and ATP production in obligate alkaliphilic Bacillaceae: insights into cytochrome c and H+ transport mechanisms - Yumoto, Isao (Frontiers in Microbiology, 2025)
Alkaliphilic Bacillaceae strains likely utilize a limited number of free H+, producing ATP through an H+-based electrochemical membrane potential more efficiently than neutralophiles do. One possible mechanism responsible for this involves a structure that accumulates H+ through a hydrogen-bonding network formed by water molecules and the acidic, amido-, and hydroxyl- groups of amino acids located at the N-terminal site of membrane-bound cytochromes c, which are specifically found in obligate alkaliphiles. The segment of cytochromes c facilitates the formation of an H+-capacitor at the outer membrane surface. The H+-capacitor would produce an additional unbalanced vertical force to drive F1F0-ATP synthase via H+ concentrations and electrical charges across the membrane. Accumulated H+ ions are transferred from cytochrome c to the H+ influx gate of the a-subunit of F1F0-ATP synthase. However, the relative abundance of protonable basic amino acids at this site is low, suggesting that H+ transfer occurs via a membrane-bound protein containing the DUF2759 domain. This protein exposes basic amino acids that outnumber the deprotonatable acidic amino acids, effectively recruiting H+ from cytochrome c near the H+ influx gate of F1F0-ATP synthase. The disparity in abundance between acidic and basic amino acids within the H+ carrier segment may play a crucial role in determining H+ transfer efficiency. In alkaliphiles, significant gaps in H+ release or acceptance exist between the outer membrane and the intracellular side of F1F0-ATP synthase. This indicates that the hydrophilic segments involved in H+ transfer are specifically designed to enhance the performance of F1F0-ATP synthase. This hypothetical mechanism for the effective transportation of accumulated H+ to the N-terminal region of the cytochrome c amino acid sequence is essential for ATP production in obligate alkaliphilic Bacillaceae. The unique bioenergetic configuration of these alkaliphiles is evident in their high maximum ATP production rates. Maximizing the activity of F1F0-ATP synthase can be achieved through efficient H+ transport and a high transmembrane electrical potential (ΔΨ), particularly in environments where H+ availability is limited.